Business Data Ethics Emerging Models for Governing AI and Advanced Analytics - Hirsch, Dennis; Bartley, Timothy; Chandrasekaran, Aravind; Norris, Davon; Parthasarathy, Srinivasan; Turner, Piers Norris; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2024)
This open access book explains how leading business organizations attempt to achieve the responsible and ethical use of artificial intelligence (AI) and other advanced information technologies. These technologies can produce tremendous insights and benefits. But they can also invade privacy, perpetuate bias, and otherwise injure people and society. To use these technologies successfully, organizations need to implement them responsibly and ethically. The question is: how to do this? Data ethics management, and this book, provide some answers. The authors interviewed and surveyed data ethics managers at leading companies. They asked why these experts see data ethics as important and how they seek to achieve it. This book conveys the results of that research on a concise, accessible way. Much of the existing writing on data and AI ethics focuses either on macro-level ethical principles, or on micro-level product design and tooling. The interviews showed that companies need a third component: data ethics management. This third element consists of the management structures, processes, training and substantive benchmarks that companies use to operationalize their high-level ethical principles and to guide and hold accountable their developers. Data ethics management is the connective tissue makes ethical principles real. It is the focus of this book. This book should be of use to organizations that wish to improve their own data ethics management efforts, legislators and policymakers who hope to build on existing management practices, scholars who study beyond compliance business behavior, and members of the public who want to understand better the threats that AI poses and how to reduce them.
1. What is AI Ethics Management and Why Does it Matter? -- 2. AI Can Injure People and Damage Business Reputation -- 3. Why Companies Pursue AI Ethics Management -- 4. How to Draw Substantive Lines Between Ethical, and Unethical, Uses of AI -- 5. Management Structures and Processes for Achieving Responsible and Ethical AI -- 6. The Next Stage: AI for the Social Good -- 7. Conclusion.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Information technology -- Law and legislation; Mass media -- Law and legislation; Private international law; Conflict of laws; International law; Comparative law; Artificial intelligence; Business ethics; Corporate governance; IT Law, Media Law, Intellectual Property; Private International Law, International and Foreign Law, Comparative Law; Artificial Intelligence; Business Ethics; Corporate Governance